Faces of Japan : - Mente, Boye de (Simpson Doyle & Co., 1966)
The purpose of the essays making up this book is to discuss some of the more provocative Japanese customs and characteristics which are often misunderstood by Westerners, bringing out the particular Japanese values and standards that apply to each of the subjects concerned.